An orchestrating role of mitochondria in the origin and development of post-traumatic stress disorder - Lushchak, Oleh; Strilbytska, Olha; Koliada, Alexander; Storey, Kenneth B. (Frontiers in Physiology, 2023)
Post-traumatic stress disorder (PTSD) is one of the most discussed and actively researched areas in medicine, psychiatry, neurophysiology, biochemistry and rehabilitation over the last decades. Multiple causes can trigger post-traumatic stress disorder. Humans subjected to violence, participants in hostilities, victims of terrorist attacks, physical or psychological persecution, witnessing scenes of cruelty, survival of natural disasters, and more, can strongly affect both children and adults. Pathological features of post-traumatic stress disorder that are manifested at molecular, cellular and whole-organism levels must be clearly understood for successful diagnosis, management, and minimizing of long-term outcomes associated with post-traumatic stress disorder. This article summarizes existing data on different post-traumatic stress disorder causes and symptoms, as well as effects on homeostasis, genetic instability, behavior, neurohumoral balance, and personal psychic stability. In particular, we highlight a key role of mitochondria and oxidative stress development in the severity and treatment of post-traumatic stress disorder. Excessive or prolonged exposure to traumatic factors can cause irreversible mitochondrial damage, leading to cell death. This review underlines the exceptional importance of data integration about the mechanisms and functions of the mitochondrial stress response to develop a three-dimensional picture of post-traumatic stress disorder pathophysiology and develop a comprehensive, universal, multifaceted, and effective strategy of managing or treatment post-traumatic stress disorder.